UKURAN PERUSAHAAN, PROFITABILITAS, DAN FINANCIAL LEVERAGE TERHADAP PENGUNGKAPAN TANGGUNG JAWAB SOSIAL PERUSAHAAN HIGH PROFILE DI BEI - Herman Darwis (Jurnal Keuangan dan Perbankan, 2009)
This study aimed to give empirical evidence that company size, profitability andfinancial leverage influenced social responsibility disclosure. Research finding proved thatcompany size significantly and positively influenced corporate social responsibility disclosure.It was based on agency theory that the bigger a company was the bigger its agency cost was.To reduce such agency cost, a company tended to disclose information extensively. Companysprofitability had negative and insignificant association. This study was in conflict with legitimacytheory that profitability had a negative influence to corporate social responsibility disclosure.Financial leverage had no influence to corporate social responsibility disclosure. This studyfailed to support agency theory that predicted a company with higher leverage ratio woulddisclose more information because agency cost of a company with such capital structure wouldbe higher.